Adjusting the base of support and trunk orientation in children with neuromotor disorders - Immediate effects on maximal respiratory pressures - Rocha, Isabella Morgado (2022)
The ventilatory and posturl relationship results from the dual role of the central nervous system which, in case of dysfunction, can induce changes in the respiratory and neromusculoskeletal systems. This study aims to investigate the influence of modifying the base of support and trunk orienttaion in sitting position, through proprioceptive afferences, on Maximal Respiratory Pressures (MRP) in children with central nervous system dysfunction. In addition, it was intended to verify the impacto f the type of brething (nasal or oral) and motor classification (spastic or non-spastic). Pre-experimental longitudinal study, consisting of 10 volunteers, ages between 6 and 18-year-old with central nervous system dysfunction. Maximal respiratory pressures and crânio-cervical-trunk orientation were measured before (MO) and immediately after (M1) physiotherapy intervention, based on the modification of the base of support and, consequentely, trunk orientation, through proprioceptive afferences in a sitting position. With the intervention, there were significant diferences in both Maximal Inspiratory pressure (MIP) and Maximal Expiratory Pressure (MEP) (MIPMO=25.00±29.0 vs MIPM1=33.50±42.0; p=0.016 and MEPMO35.50±42,00 vs MEPM1=38,00±27,00; p=0,016) and in the craniocervical angle (CA) (CAMO=32.35±7.73 vs CAM1=41.09±9.80; p=0.010). There also seem to be diferences between the maximal inspiratory pressure in relation to the type of breath (p=0.038), ando f motor condition (p=0.032). Maximal respiratory pressures appear to be influenced by the intervention. In addition, the intervention may have differently influenced the maximal inspiratory pressure of children with nasal versus oral breathing, as well as the spastic versus non-spastic motor pattern.